CELLULAR COMPOSITION OF LYMPHOID TISSUE OF PEYER'S PATCH OF DUODENUM IN DUCKS - Tetiana Mazurkevych (Ukrainian Journal of Veterinary Sciences, 2020)
The aim of our research was to study the cell composition of the lymphoid tissue of the duodenal Peyer's patch of the ducks in age-related aspects. Among the cells of the lymphoid tissue of the duodenal Peyer's patch are immunoblasts, lymphocytes, proplasmocytes, and plasma cells, monocytes and macrophages, epithelial cells, reticular cells, erythrocytes, granulocytes, fibroblasts, and M-cells. The content of populations of these cells is not the same. Lymphocytes in the preparations-imprints are found the most. They are represented by small, medium, and large forms. Small lymphocytes were found in the largest number, and large ones – in the smallest. The content of small lymphocytes decreases unevenly with the age of ducks, and medium and large lymphocytes – increases unevenly. The content of immunoblasts in the lymphoid tissue of the duodenal Peyer's patch of ducks is less than that of lymphocytes. This index decreases unevenly from the 1st to the 420 days of age of birds. Proplasmocytes and plasmocytes are found in the lymphoid tissue of the duodenal Peyer's patch of ducks in small numbers from the 15th day of age. Their content increases significantly with the increasing of the birds’ age. The content of macrophages and monocytes in the lymphoid tissue of the duodenal Peyer's patch of ducks is insignificant. Uneven increase of this indicator is registered from the 1st to the 420 days of age of birds. The content of reticular cells cannot be calculated because they are covered by lymphoid cells, and fibroblasts, erythrocytes, granulocytes, and M-cells that occur in the imprint preparations in small quantities cannot be statistically processed